2018
DOI: 10.1155/2018/4582130
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Thioredoxin‐Binding Protein‐2 (TBP‐2) in Different Diseases

Abstract: Thioredoxin-binding protein-2 (TBP-2) has an important role in the redox system, but it plays a different role in many different diseases (e.g., various cancers, diabetes mellitus (DM), cardiovascular disease, and cataracts) by influencing cell proliferation, differentiation, apoptosis, autophagy, and metabolism. Distinct transcription factors (TFs) stimulated by different factors combine with binding sites or proteins to upregulate or downregulate TBP-2 expression, in order to respond to the change in the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 74 publications
1
33
0
Order By: Relevance
“…In the present study, we used the autophagic inhibitor ba lomycin A1 to block the its last stage which is the fusion of autophagosomes and lysosomes and autophagic inhibitor wortmannin to inhibit autophagy at the initiation stage. Our data indicated that Trx-1 mainly regulates autophagy in the initiation stage and facilitates autophagic induction, which consistent with our previous nding on the autophagic ux induction by TBP-2 in the initiation stage [18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we used the autophagic inhibitor ba lomycin A1 to block the its last stage which is the fusion of autophagosomes and lysosomes and autophagic inhibitor wortmannin to inhibit autophagy at the initiation stage. Our data indicated that Trx-1 mainly regulates autophagy in the initiation stage and facilitates autophagic induction, which consistent with our previous nding on the autophagic ux induction by TBP-2 in the initiation stage [18].…”
Section: Discussionsupporting
confidence: 93%
“…Our previous study showed oxidative stress induced autophagic response of LECs with increased LC3-II, p62, and GFP/mCherry-LC3 puncta. Overexpression of TBP-2 further strengthens autophagic response in the initiation stage, which is mTOR-independent and probably caused by the dephosphorylation of Akt under oxidative stress [18]. In the present study, we used the autophagic inhibitor ba lomycin A1 to block the its last stage which is the fusion of autophagosomes and lysosomes and autophagic inhibitor wortmannin to inhibit autophagy at the initiation stage.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, VDUP1 has been originally identified in HL-60 cells as one of the proteins, the gene of which is strongly induced by vitamin D ( Figure 5 ) [ 397 , 398 ]. In turn, VDUP1 has been isolated in studies aimed to characterize the endogenous inhibitor of the reactive oxygen species (ROS) scavenger system of Thioredoxin (Trx) and for this, it was also called TXNIP [ 399 ] or Thioredoxin Binding Protein 2 (TBP2) [ 400 ].…”
Section: Vitamin D and Neurofibromatosismentioning
confidence: 99%
“…Furthermore, TBP-2 inhibits Akt/Bcl-xL signaling, independent of mTOR, to facilitate the initial stage of autophagy [80]. ese findings will inspire more studies to explore target therapies for preventing autophagy induced by ROS in LECs and prevent cataract formation in elderly people [83].…”
Section: Cataractmentioning
confidence: 99%